Growing but not transforming: Fragmented ruling coalitions and economic developments in Uganda - Anne Mette Kjær; Mesharch Katusiimeh (Danish Institute for International Studies (DIIS), 2012)
In this paper, we analyze Uganda's development through a political economy lens that emphasizes the nature of the ruling coalition. In theory, according to Khan (2010), a relatively stable ruling coalition without any strong opposing factions should be able to decide and implement growth-enhancing strategies to promote structural transformation, because there will be no strong faction resisting such strategies. However, this has not happened to any significant extent in Uganda. The ruling coalition has been stable, and there have been no strong excluded factions with enough holding power to seriously challenge the regime. The northern region, particularly the Acholi region, has been excluded from power and influence, and it is in the Acholi area that the Lord's Resistance Army (LRA), a rebel group, has been active and rampaging among the local population. The regime has been criticized for not adequately protecting the Acholi population. However, with the LRA in Congo at the moment of writing (continuing its assaults on local populations), peace (albeit temporary) has finally been established in the north, and the region has seen a period of growth since 2006. Museveni gained more votes from the region in the 2011 elections than he has ever done before (Uganda Electoral Commission, 2011).
Keywords: 330; Wirtschaftsreform; Regierungskoalition; Entwicklung; Uganda